2018
DOI: 10.3846/bme.2018.2142
|View full text |Cite
|
Sign up to set email alerts
|

The Increasing Role of It Auditors in Financial Audit: Risks and Intelligent Answers

Abstract: Abstract. Financial auditing cannot be imagined without the involvement of IT specialists since business processes are designed to be served by IT components such as ERP systems, online customer-facing applications, databases etc. Financial auditors therefore exposed to IT system and control reliance want to gain reasonable assurance that data and transactions stored in IT systems cannot be modified, access is controlled, and there is no suspicion of any fraud at business organizations. The paper tries to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
0
9
0
3
Order By: Relevance
“…In order to resolve the contradictions, a coordination mechanism between financial auditing and financial supervision should be established, making full use of financial risk management techniques, enhancing the data processing capabilities of audit workers, and giving full play to auditing. Relevant scholars also believe that financial auditing should give full play to its unique advantages of independence, work with financial regulatory agencies to play a re-supervision function, and jointly maintain national financial security by strengthening the mutual cooperation between government financial auditing agencies and national financial regulatory agencies [ 30 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…In order to resolve the contradictions, a coordination mechanism between financial auditing and financial supervision should be established, making full use of financial risk management techniques, enhancing the data processing capabilities of audit workers, and giving full play to auditing. Relevant scholars also believe that financial auditing should give full play to its unique advantages of independence, work with financial regulatory agencies to play a re-supervision function, and jointly maintain national financial security by strengthening the mutual cooperation between government financial auditing agencies and national financial regulatory agencies [ 30 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Andrew Clark examined AI development procedures in terms of audit considerations and published several articles how internal or external auditors shall adjust their audit plans when it comes to AI (Clark, 2016(Clark, , 2017(Clark, , 2018. Auditing is an important part of risk assessment, as the primary function of the audit team is to obtain reasonable assurance whether internal controls are operating effectively that are an option to reduce business risk to an acceptable level (Barta, 2018b). Thus, developing audit procedures to obtain assurance over internal controls is indispensable part of the organisational risk management framework and so as to appropriately assess risk, auditing must be in place and be performed in a timely manner.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, Omoteso (2012) and Barta (2018) examined the use of artificial intelligence in the procedures of auditing in light of auditing and audit standards. They showed that auditing procedures require development in the environment of modern business and auditors should increase their efforts to have an effective role in judgment and control.…”
Section: Previous Studiesmentioning
confidence: 99%